Bonds of Union - Isabelle Bour, Antoine Mioche (dir.) (Presses universitaires François-Rabelais, 2005)
The appearance and development of a ""Four Nations"" slant on British history over the last two decades has in many ways pointed up ""the Union"" as an essential component of the national history or histories of the British Isles. ""Four Nations"" historians, however, have tended to focus exclusively on the United Kingdom as the core of either a nascent or a now defunct Empire. History is variously invoked to account for the emergence of the British dynastic state, explain its (to some) puzzling en...